Ultrasmall and ultrafast all-optical modulation based on a plasmonic lens - Yue, Song; Li, Zhi; Chen, Jianjun; Qihuang Gong (APPLIED PHYSICS LETTERS, 2011)
By exciting a plasmonic lens with femtosecond laser and utilizing the optical nonlinearity of the gold, an ultrasmall and ultrafast all-optical modulation spot was achieved inside a thin gold film. Near-field pump-probe measurements indicated a modulation spot size of about 600 nm, and a response time of about 1.5 ps. Even smaller spot size of about 300 nm was inferred from numerical simulations, beyond the diffraction limit given an incident wavelength of 1000 nm. Moreover, the optical nonlinearity and the modulation depth were increased by one order of magnitude at the focus compared to that at positions without structures. (C) 2011 American Institute of Physics. [doi:10.1063/1.3581895]